{Collection of menopause data in studies of women living with HIV: A systematic literature review.} - Graham, Emma Eileen; Michala, Lina; Hachfeld, Anna; Moseholm, Ellen (HIV medicine, 2024)
OBJECTIVES: An increasing number of women living with HIV are transitioning through midlife and menopause. Women living with HIV may experience earlier menopause and a higher symptom burden than women without HIV, but more evidence is needed. Data collection on menopause in women living with HIV is scarce and often not standardized. We sought to assess how menopause data are collected in cohorts and studies of women living with HIV. METHODS: This was a literature review conducted within the PubMed database. We included original studies and cohorts assessing menopause and/or menopausal symptoms in women living with HIV. Study characteristics and menopause data collection, including the definition of menopause, symptom assessment tools, and measurement of biomedical parameters, were noted and summarized systematically in data tables. RESULTS: We included 40 articles describing 37 separate studies published between 2000 and 2023; 27 of these were conducted in high-income countries, the majority in the USA (n = 16). Ten studies were from low- and middle-income countries; four of these were conducted in Brazil. In 20 studies, menopause was defined according to the World Health Organization's definition of over 12 months of amenorrhea. Twelve studies used the Menopause Rating Scale to characterize menopausal symptoms, five studies used other specified symptom assessment tools, and 12 studies used a study-specific tool. CONCLUSIONS: Menopause data collection in women living with HIV is heterogeneous. We propose that standardized tools should be used to enable comparisons between studies and countries, thereby improving the quality of research and clinical treatment. Further research into the validity of menopausal symptom scoring tools is warranted.
Keywords: Brazil; Complications; Data Collection; Female; HIV Infections; Humans; menopause